Advances in proton exchange membrane fuel cell with dead-end anode operation: A review - Kurnia, J.C. (Elsevier Ltd, 2019)
To improve fuel utilization and reduce complexity of polymer electrolyte fuel cell especially for automotive application, dead-end anode operation is desirable. In this operating mode, the anode outlet is closed to achieve nearly 100 fuel utilization. Despite its great potential, operating the fuel cell in a dead-end anode mode brings consequence of nitrogen crossover and liquid water back diffusion which accumulate in the anode, hindering contact between hydrogen fuel with the catalyst inducing fuel starvation. This fuel starvation not only deteriorates fuel cell performance but also degrades the cell integrity by inducing carbon corrosion. To address these issues and achieve optimum operation conditions for the fuel cell, numerous studies on the performance of the dead-end anode fuel cell have been conducted, several key parameters have been evaluated and various mitigation strategies have been proposed. However, the dead-end anode fuel cell has not reached its mature commercialization stage and more research and development is required. To assist further research and development of the dead-end anode fuel cell and expedite its mass application, it is imperative to grasp and discuss the main findings of the previously reported studies. At the moment, no review paper on the dead-end anode fuel cell is available. Therefore, this paper is presented to comprehensively review the development and advancement of dead-end anode fuel cells. In addition, the required research and development for further advancements of the field are also outlined and discussed. Â© 2019